DOCTOR BEHAVIOR IN FILLING THE MEDICAL RESUME SHEET IN BAGAS WARAS HOSPITAL, KLATEN - Anggit Budiarto; Mahendro Prasetyo Kusumo; Winy Setyo Nugroho (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The hospital as one of the health service facilities, is part of the health resources that were needed in supporting the implementation of health efforts. The writing of patient diagnosis is the responsibility of the treating physician and should not be represented. The phenomenon found in the initial survey of Regional General Hospital Bagas Waras Klaten obtained many incomplete resume forms. The purpose of this research is to know the doctor's behavior on the filling of the in-patient resume sheet data at  BagasWaras HospitalKlaten. This research was a qualitative research with case study approach. Respondents in this study were DPJP Specialist Doctor, Medical Record Officer and Hospital Director. The data obtained from interviews, FGDs, observations and documentation and collected and grouped based on existing indicators, as well as based on existing facts and also on critical thoughts to obtain a weighted result. Based on the results of the doctor's observation through the medical resume sheet for 3consecutive months which had been submitted to the medical record, it appeared that medical resume filled by the doctor after the patient finished treatment was still low, from 217 files, which was incomplete as much as 125 with a percentage of 41%. It was due to lack of cooperation between doctors and nurses in filling medical resume. In addition, the incomplete medical resume was due to the nonoperation of the Standard Operational Procedure (SOP) which regulated the filling of medical resumes, the absence of regulations, sanctions for doctors who did not fill the medical resume so the doctors lazily fill medical resume. The doctor's behavior in completing the medical resume sheet is still low.  Keywords: Medical Resume, Behavior Physician